2019
DOI: 10.1186/s12886-019-1234-7
|View full text |Cite
|
Sign up to set email alerts
|

Epibulbar complex choristoma with simultaneous involvement of eyelid: a case report

Abstract: BackgroundEpibulbar complex choristoma, a rare congenital epibulbar tumor, has many diverse forms. Reviewing the literature, it can present clinically as either a circumferential or isolated epibulbar mass, limbal tumor, lateral canthal mass, aggregate of ectopic cilia in the upper eyelid, eyelid mass mimicking chalazion, or lacrimal caruncle mass. The management depends on the extent of involvement, the risk of amblyopia, and cosmetic concerns. Here, we report an atypical presentation of epibulbar complex cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…[9,10] While it occurs most commonly in supratemporal subconjunctival space attached to or separate from sclera, it can also be found at various locations such as perilimbal area, lateral canthus, extraocular muscle insertions, and tarsal plate. [11][12][13][14] Some explanations for the of epibulbar osseous choristoma have been proposed. Duke Elder first proposed the existence of secondary ossification centers of the orbital bones which very rarely could remain isolated, giving rise to small bones identified as osseous choristoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[9,10] While it occurs most commonly in supratemporal subconjunctival space attached to or separate from sclera, it can also be found at various locations such as perilimbal area, lateral canthus, extraocular muscle insertions, and tarsal plate. [11][12][13][14] Some explanations for the of epibulbar osseous choristoma have been proposed. Duke Elder first proposed the existence of secondary ossification centers of the orbital bones which very rarely could remain isolated, giving rise to small bones identified as osseous choristoma.…”
Section: Discussionmentioning
confidence: 99%
“…In review of literature, CT images of epibulbar osseous choristoma revealed a cystic mass with fat-like low-density and a high-density radio-opaque mass which is indicative of a calcium component. [8,11,12,[17][18][19][20][21][22][23][24]26] This differentiates epibulbar osseous choristoma from low-density lesions like fat, dermolipoma, or epibulbar dermoid and helps predict the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated eyelid complex choristoma containing ectopic cilia and lacrimal gland tissue has been also reported. [ 1 ] Eyelid complex choristomas may accompany other ocular lesions including an epibulbar complex choristoma,[ 8 ] choroidal osteoma, and an epidermal nevus syndrome. [ 6 ] In our case, the patient had no systemic association.…”
Section: Discussionmentioning
confidence: 99%